Recent illicit drug use among psychiatric patients in Brazil: a national representative study - Miriam Almeida Nahas (Revista de Saúde Pública, 2017)
OBJECTIVE: To estimate factors associated to illicit drug use among patients with mental illness in Brazil according to gender. METHODS: A cross-sectional representative sample of psychiatric patients (2,475 individuals) was randomly selected from 11 hospitals and 15 public mental health outpatient clinics. Data on self-reported illicit drug use and sociodemographic, clinical and behavioral characteristics were obtained from face-to-face interviews. Logistic regression was used to estimate associations with recent illicit drug use. RESULTS: The prevalence of any recent illicit drug use was 11.4%. Men had higher prevalence than women for all substances (17.5% and 5.6%, respectively). Lower education, history of physical violence, and history of homelessness were associated with drug use among men only; not professing a religion was associated with drug use in women only. For both men and women, younger age, current hospitalization, alcohol and tobacco use, history of incarceration, younger age at sexual debut, and more than one sexual partner were statistically associated with illicit drug use. CONCLUSIONS: Recent illicit drug use among psychiatric patients is higher than among the general Brazilian population and it is associated with multiple factors including markers of psychiatric severity. Our data indicate the need for the development of gender-based drug-use interventions among psychiatric patients in Brazil. Integration of substance use treatment strategies with mental health treatment should be a priority.